Ghosts - Telgemeier, Raina; Lamb, Braden (New York : Graphix, an imprint of Scholastic, 2016)
Catrina and her family have moved to the coast of Northern California for the sake of her little sister, Maya, who has cystic fibrosis--and Cat is even less happy about the move when she is told that her new town is inhabited by ghosts, and Maya sets her heart on meeting one.
GN 300
Keywords: Sisters -- Comic books, strips, etc; Ghosts -- Comic books, strips, etc; Moving, Household -- Comic books, strips, etc; Families -- California, Northern -- Comic books, strips, etc; Graphic novels; Cystic fibrosis -- Comic books, strips, etc; California, Northern -- Comic books, strips, etc